(untitled) (Faridpur Medical College Journal, 2013)
Lepra Reactions (LR) comprises immunologically mediated inflammatory states that cause considerable morbidity. Type-2 LR occurs exclusively in patients with the lepromatous end of the leprosy spectrum (BL-LL). In 90% of the cases it follows during or after completion of chemotherapy, generally within 2 years. Here we report a case of type-2 LR. He is a twenty years old fisherman with history of hypopigmented skin lesion 3 years back and was treated as a case of lepromatous Leprosy (LL). After six months of completion of treatment he developed type-2 LR presenting with recurrent bouts of fever, polyarthritis, erythema nodusum, orchitis, mononeuritis multiplex and was treated in Faridpur Medical College Hospital (FMCH) on three occasions within last one and half years. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13524 Faridpur Med. Coll. J. 2012;7(2):93-97